(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This paper depicts Philip Larkin’s intriguing insight of his complex mind. It does not only show hisinclination to nature and pastoral life but his attitudes towards religion, love and marriages. ‘WeddingNights’ are expected to be an unique experiences but Larkin expresses his doubt whether suchhappiness can endure forever. Larkin’s love poems seem to bring sexual fulfilment and relief butseveral sexual acts are deceptive and false. Larkin opines that marriage is an act of losing one’sfreedom and facing intrinsic failures. Marriages result in disillusion and disappointments.